Extremely Sensitive SERS Detection through the One-Step Fabrication of a Composite Nanostructure of Substrate and Analyte. (17th October 2015) - Yang, Xing; Wang, Qiong; Fan, Jiaorong; Zhang, Min; Zhou, Zhaoying; Ji, Jianlong
Abstract : A general surface-enhanced Raman spectroscopy (SERS) detection method was established through the one-step fabrication of a composite nanostructure of substrate and analyte to enable extremely sensitive biochemical detection. Compared with commonly used stepwise SERS detection techniques, our method can effectively increase detection sensitivity because of the enrichment effect. Results showed that the lowest detection limit of our method was 10 −13 mol/L (for Rhodamine B), which was higher by five magnitudes than that obtained by stepwise detection. Our method was also easy to operate and cost effective, thereby showing potential application in trace analyses of biochemical analytes.